THE USE OF RAFT AND FOUR SQUARE STRATEGIES TO IMPROVE STUDENTS’ NARRATIVE WRITING ACHIEVEMENT - Rahmat Febriadi (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The purposes of this research were to find out whether or not there was any significant difference in narrative writing achievement between before and after the students who were taught by using RAFT strategy, significant difference in narrative writing achievement between before and after the students who were taught by using Four Square strategy and significant difference in narrative writing achievement between the students who were taught using RAFT and Four Square strategies. This study also investigated which aspects of writing that had significant contributions to the students’ achievements. The population of this study was all of the tenth graders of SMK Negeri 2 Banyuasin III in academic year 2016-2017. Forty students were selected as the sample by using purposive sampling method. They were divided equally into experimental and control groups. The experimental group was taught by using RAFT strategy, while the control group was taught by using Four Square strategy. The data were obtained from writing pretests and posttests in both groups and were analyzed by using both paired and independent sample t-test, and regression analyses. The findings showed that there were significant differences in narrative writing achievement between before and after the students were taught by using RAFT, significant differences between before and after the students who were taught by using Four Square strategy, and no significant difference in narrative writing achievement between the students who were taught by using RAFT strategy and those who were taught by using Four Square strategy. In conclusions, both strategies could be applied to improve students’ writing achievement. Keywords: Writing, narrative, RAFT, Four Square, vocational school